RGEC Analysis in Assessing The Health of Bank Before and During The Covid-19 Pandemic - Shinta Anggraeny; Iwan Suhasto; Dewi Kirowati (Politeknik Negeri Madiun, 2022)
This study aims to assess the financial performance of state-owned banks consisting of Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), Bank Savings State (BTN), Bank Mandiri. This research is a research using a quantitative approach. The object of this research is a state-owned bank listed on the Indonesia Stock Exchange for the 2018-2021 period. The data collection technique used is through the documentation method. The data source used is secondary from the annual financial statements obtained through the official website of the Indonesia Stock Exchange. The analysis technique uses the calculation of the RGEC method. The results of this study are expected to be able to show how the condition of the soundness level of state-owned banks listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period through the RGEC method is carried out. This analysis is also expected to be used as a reference for state-owned banks in assessing the soundness of banks. Aspects of the Risk Profile of state-owned banks during the 2018-2021 period are in a quite healthy with an average NPL value of 3.05%, 1.48%, 2.75%, and 3.75%, respectively. Then the average IRR values are 110.2%, 305.8%, 110.6%, and 112.8%, respectively. And lastly, the average LDR values were 89.71%, 82.49%, 105.11%, and 92.30%. The GCG aspects of state-owned banks during the 2018-2021 period are 2,2,1, and 2, so that in general they are said to be good. Aspects of BUMN bank earnings during 2018-2021 are in a healthy condition with average ROA values of 1.72%, 2.78%, 1.23%, and 0.72%, respectively. And the average NIM scores are 5.12%, 8.59%, 4.54%, and 3.86%, respectively. The capital aspect during 2018-2021 is in a healthy condition with the average CAR values of 18.69%, 22.41%, 20.46%, and 18.50%, respectively.